Penerapan Ecobrick Sebagai Solusi Untuk Mengurangi Sampah Plastik Di Lingkungan Pondok Pesantren Assunniyyah Kencong Jember - Farha Niswa Al Humaira; Garneza Merlyana Alfianti; Ayu Rahmawati; Zirly Zauda Putri; Nur Hasanah; Wahyu Hidayah; Nabilla Rahma Maharsany; Fazlul Rahman (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Waste is a problem that is always faced by all sectors, one of which is the Assunniyyah Islamic Boarding School in Jember Regency. As an educational institution, the waste problem at the Assunniyyah Islamic Boarding School in Jember Regency is mostly inorganic waste, especially plastic waste. This waste has not been used so it only ends up in landfills. This Community Service Program aims to increase awareness of students about waste and implement ecobricks as an effort to reduce plastic waste in the Assunniyyah Islamic Boarding School environment in Jember Regency. The method used starts from the inorganic waste introduction stage, the ecobrick introduction stage, and the ecobrick making training stage. The results of this program show that this training is useful. Keyword: Devotion, Ecobricks, Inorganic waste